Role of cytokine and neurotrophic factors in nicotine addiction in the conditioned place preference paradigm. (1st November 2021) - Rosa, Magda Luciana de Paula; Machado, Caroline Amaral; Oliveira, Bruna da Silva; Toscano, Eliana Cristina de Brito; Asth, Laila; de Barros, João Luís Vieira Monteiro; Teixeira, Antônio Lúcio; Moreira, Fabrício A.; de Miranda, Aline Silva
Highlights: Peripheral administration of nicotine induces CPP behavior in mice. CPP behavior is associated with reduced levels of IL-10 and IL-1β in the striatum. Hippocampal levels of neurotrophic factors may contribute for the CPP behavior. Cytokines and Neurotrophic Factors play a role in Nicotine-induced CPP behavior. Abstract: The mechanisms involved in the maintenance of cigarette smoking and nicotine reward remain unclear. Immune response might play an important role in this context. Nicotine may induce both central and systemic inflammatory responses as well as changes in the regulation of brain-derived neurotrophic factor (BDNF). The conditioned place preference (CPP) is a method used for the evaluation of nicotine-induced reward, reproducing nicotine-seeking behavior in humans. So far, there are no studies investigating the relationship between neuroinflammation and nicotine-induced CPP. This study aimed to evaluate the levels of inflammatory mediators and neurotrophic factors in key areas of the central nervous system (CNS) of mice subject to nicotine-induced CPP. CPP was induced with an intraperitoneal administration of 0.5 mg/kg of nicotine in male Swiss mice, using an unbiased protocol. Control group received vehicle by the same route. The levels of cytokines, chemokines, and neurotrophic factors were measured using Enzyme-Linked Immunosorbent Assay (ELISA) in the brain after CPP test. As expected, nicotine induced place preference behavior. In parallel, we observed increased peripheral levels of IL-6 and IL-10 alongside increased hippocampal levels of NGF but decreased GDNF in mice treated with nicotine compared to controls. In the striatum, nicotine promoted decrease of IL-1ß, IL-10 and GDNF levels, while the levels of all the mediators were similar between groups in the pre-frontal cortex. Our results provide evidence on the role of cytokines and neurotrophic factors in nicotine-induced CPP in mice.